2004
DOI: 10.1063/1.1689644
|View full text |Cite
|
Sign up to set email alerts
|

Clustering and percolation in lithium borate glasses

Abstract: Molecular dynamics simulations are carried out in xLi 2 O-(1Ϫx)B 2 O 3 glasses (xϭ0.2-0.6) at Tϭ1250 K, where cluster size distributions for Li cations and nonbridging oxygen ͑NBO͒ atoms are calculated. The existence of percolating clusters above xϭ0.3 places the percolation threshold between xϭ0.3 and 0.4 for the system under investigation, which is consistent with the abrupt increase of the diffusion coefficient of Li cations observed at xϭ0.4. It is also shown that the clusters of Li cations consist mainly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 45 publications
0
18
0
Order By: Relevance
“…In the case of silicates, these are predominantly NBOs, while NBOs as well as tetrahedrically coordinated borons (BO 4 ) both contribute in borate glasses. Recent molecular dynamics simulations [36,37] have indicated that the mobility of the alkali ions is significantly higher in the neighborhood of a NBO defect. This may by understood by the broken bond of the NBO that weakens the network locally, while the BO 4 units even strengthen the network in comparison to the trigonal units of the undoped borate network.…”
Section: Ion Conductivity Of Sputter-deposited Oxide Glassesmentioning
confidence: 99%
“…In the case of silicates, these are predominantly NBOs, while NBOs as well as tetrahedrically coordinated borons (BO 4 ) both contribute in borate glasses. Recent molecular dynamics simulations [36,37] have indicated that the mobility of the alkali ions is significantly higher in the neighborhood of a NBO defect. This may by understood by the broken bond of the NBO that weakens the network locally, while the BO 4 units even strengthen the network in comparison to the trigonal units of the undoped borate network.…”
Section: Ion Conductivity Of Sputter-deposited Oxide Glassesmentioning
confidence: 99%
“…The NBO sites tend to form an assemblage, a so-called cluster, and percolate from one edge to the opposite so as to form a conduction pathway ͑ionic diffusion channel͒. 13 If the population of NBO sites is in the vicinity of the percolation threshold P c ͑24.5% for site percolation of cubic lattice 14 ͒, NBO clusters of various sizes accumulate inside the glass layer. Here, the feature length of the largest cluster is defined as .…”
Section: P14mentioning
confidence: 99%
“…Clustering processes were also reported in other borate glass systems [19][20][21], but detected with different techniques. It is observed that the concentration where this behaviour is reported depends on the doping ion.…”
Section: Discussionmentioning
confidence: 79%